Feature Estraction In Automatic Shape Recognition System. - Salam, Rosalina Abdul; Talib, Abdullah Zawawi; Sumari, Putra; Rodrigues, Marcos Aurelio (2004)
Advances in technology have made it easier to obtain and store large quantities of data.